ANALISIS KESESUAIAN PERMUKIMAN TERHADAP BAHAYA LONGSORAN DENGAN MENGGUNAKAN TEKNOLOGI SISTEM INFORMASI GEOGRAFI DI KECAMATAN TEMBALANG KOTA SEMARANG - Benardi, Andi Irwan (Universitas Negeri Semarang, 2015)
The aim of this research which seeks: (1) Disclose the suitability of land for residential areas in District Tembalang (2)Disclose the evaluation of suitability of land for residential areas in District Tembalang and (3) Establish the area ofsettlements in the District Tembalang. Data analysis method is through the method of overlaying (overlay) maps andmethods pengharkatan (scoring). The results showed that in 313 land units District Tembalang there are three (3) classland units with three (3) the suitability of land, among others: (1) Units of land class I with land suitability VerySuitable (S1) explained that land units with conditions excellent remedy settlements. This region has an area of 1,913km2 with a percentage 2:58%, ie inhibiting factor parameter wrinkle development of land and soil bearing capacity. (2)Unit class II land with land suitability Suitable (S2) explained that land units with appropriate conditions for thelocation of settlements with little obstacle. The total area is about 68 673 km2 with a percentage of 92.57%. inhibitingfactors include parameter wrinkle development of land, the carrying capacity of the soil, the soil surface drainage,erosion, flood hazard. (3) Unit Class III lands with land suitability accordance Marginal (S3) explained that land unitswith the medium (appropriately enough) to settlements with some inhibiting factors. Inhibiting factor is the slopeparameter, flowers wrinkle land, the carrying capacity of the soil, erosion, groundwater depth, access to groundwater,the number of grooves. This region has an area of 3,597 km2 with a percentage of 4.85%.